Implementasi Metode Scrum Pada Aplikasi Penjualan Peta Dan Buku (Studi Kasus Pada CV Ubo Rampe Palwoko) - Fajar Agustini (LPPM Universitas Bina Sarana Informatika, 2023)
The Scrum method is a methodology included in agile software development. Scrum is considered to be able to produce good quality software in accordance with the wishes of users, can be used in large and small projects, and is easy to adopt changes. The stages of scrum activity include product backlog, sprint backlog, daily scrum, sprint review, and sprint retrospective. Roles in Scrum include product owner, scrum master, and development team. Scrum has structured and iterative stages, so that if the product in the first sprint does not meet the needs, then in the next sprint a system can be developed according to the user's evaluation. The results obtained in the sales accounting information system using the scrum method are proven to be able to overcome product promotions, sales data processing, produce reports that are more accurate and have fewer errors